HUBUNGAN KEBIJAKAN KEPALA SEKOLAH DALAM PEMANFAATAN IT DAN MOTIVASI KERJA TERHADAP KINERJA PEMBELAJARAN GURU MADRASAH IBTIDAIYAH - Samsudin Samsudin; Nurasiah Jamil (Akademika : Jurnal Teknologi Pendidikan, 2023)
This takes into account the decision points 1) There is a significant relationship between the director's approach to creative use of data and the academic performance of the faculty members at Madrasah Ibtidaiyah in Parung district . 2) There is a remarkable relationship between work inspiration and academic performance of Madrasah Ibtidaiyah instructors in Parung locality. 3) The relationship between the principal's disposition in the innovative use of data and work inspiration with the learning outcomes of Madrasah Ibtidaiyah faculty members in the Parung region. This examines the research strategies used and the methods of correlation. The test method uses a moderate test method such that a reasonable number of counts is 60 checks. Collect information about learning outcomes using reports and survey responses. At this stage, the information search strategy used expressive evaluation and inferential factual evaluation. It turns out that 1) There is a significant relationship between the approach of school principals to the use of information technology and the academic performance of instructors in essential schools in the Parung region . 2) There is a remarkable relationship between work inspiration and academic performance of Madrasah Ibtidaiyah instructors in the Parung region. 3) There is a general relationship between the director's arrangement for creative use of data and the inspiration for the work done by the instructors Madrasah Ibtidaiyah in the Parung region.